The Effect of Work Competence and Work Discipline on Contract Employee Performance with Motivation as Intervening Variable: The Case of Ogan Ilir Regional Disaster Management Agency - Arifqi Bahara; Fatimah Fatimah; Trisniarty Adjeng Moelyati (International Journal of Business, Management and Economics, 2026)
This study aims to determine the effects of competence and work discipline on the performance of contract employees at the Regional Disaster Management Agency (BPBD) of Ogan Ilir Regency, with work motivation as an intervening variable. This research is associative. The variables used by the researcher are competence, work discipline, work motivation, and performance, which are developed into 12 indicators. The population of this study consists of all contract employees of BPBD Ogan Ilir Regency, totaling 139, while the sample comprises 120 contract employees selected using Simple Random Sampling. The data used in this study are primary data collected through questionnaires. The data analysis technique employed is Structural Equation Modeling (SEM) using the LISREL application program. The results of this study indicate that: 1) Competence has a significant effect on the work motivation of contract employees at BPBD Ogan Ilir Regency. 2) Work discipline has a significant effect on the work motivation of contract employees at BPBD Ogan Ilir Regency. 3) Work motivation has a significant effect on the performance of contract employees at BPBD Ogan Ilir Regency. 4) Competence does not have a significant effect on the performance of contract employees at BPBD Ogan Ilir Regency. 5) Work discipline does not have a significant effect on the performance of contract employees at BPBD Ogan Ilir Regency. These findings indicate that work motivation acts as an intervening variable in the relationship between competence and work discipline on the performance of contract employees at BPBD Ogan Ilir Regency.